Investigating the effectiveness of an online acceptance and commitment therapy (ACT) intervention versus a waiting list control condition on pain interference and quality of life in adults with chronic pain and multimorbidity: protocol for a randomised controlled trial. Issue 5 (9th May 2019) - Slattery, Brian W; O'Connor, Laura L; Haugh, Stephanie; Barrett, Katie; Francis, Kady; Dwyer, Christopher P; O'Higgins, Siobhan; Caes, Line; Egan, Jonathan; McGuire, Brian E
Abstract : Introduction: Multimorbidity refers to the presence of two or more chronic health conditions within one person, where no one condition is primary. Research suggests that multimorbidity is highly correlated with chronic pain, which is pain lasting longer than 3 months. Psychotherapeutic interventions for people living with chronic illness have resulted in reduced symptom reporting and improved psychological well-being. There is a dearth of research, however, using online psychotherapy for people living with multimorbidity where chronic pain is a central condition. This study will compare the effectiveness of an online acceptance and commitment therapy (ACT) intervention with a waiting list control condition in terms of improving health-related quality of life (HRQoL) and reducing levels of pain interference in people with chronic pain and at least one other condition. Methods and analysis: 192 adult participants with non-malignant pain that persists for at least 3 months and at least one other medically diagnosed condition will be randomised to one of two study conditions. The experimental group will undergo an eight-session internet-delivered ACT programme over an 8-week period. A waiting list group will be offered the ACT intervention after the 3-month follow-up period. HRQoL and pain interference will act as the primary outcomes. Data will be analysed using a linear mixed model and adjusted to account for demographic and clinical variables as necessary. A Study Within a Trial will be incorporated to examine the effect on recruitment and retention of showing participants an animated educational video. Ethics and dissemination: Ethical approval has been granted by the Research Ethics Committee of the National University of Ireland, Galway. Dissemination of results will be via peer reviewed journal articles and conference presentations. Trial registration number: ISRCTN22343024 .